PENGARUH DEWAN DIREKSI KOMISARIS INDEPENDEN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP HARGA SAHAM MELALUI RETURN ON EQUITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Naufal Hirmawan Tarihoran; Liza Novietta; Iman Indrafana K.H (Bisnis-Net, 2023)
AbstractThis study aims to determine the effect of the board of directors, independent commissioners and institutional ownership on return on equity partially. To determine the effect of return on equity mediating the effect of the board of directors, independent commissioners and institutional ownership on stock prices partially. The total population in ithis study was 195 with a sample of 310 data observations. The analysis technique used is Path Analysis.The results showed that the board of directors had a significant positive effect on stock prices, independent commissioners had a significant positive effect on stock prices, institutional ownership had no effect on stock prices, return on equity had no effect on stock prices, the board of directors had no effect on return on equity, independent commissioners has a significant positive effect on return on equity, institutional ownership has no effect on return on equity, return on equity does not mediate the relationship between the board of directors and stock prices, return on equity does not mediate the relationship between independent commissioners and stock prices and return on equity does not mediate the relationship between institutional ownership of share prices in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2017-2021 period.Keywords: dewan rediksi, komisaris independent, return on equity